Forecasting Rainfall and Temperature Trends in Bangladesh Based on Historical Data Analysis - Hore, Shoma; Kamrul, Md Kamruzzaman; Alim, Mosharof Al; Hore, ripon (Department of Geography Education, University of Jember, 2025)
This study examined temperature and precipitation trends and spatial variations over a 40-year period at 34 meteorological stations in Bangladesh. Climate variability was assessed using a variety of statistical techniques, such as geographic information systems (GIS), inverse distance weighting (IDW) interpolation, linear regression, and coefficient of variation. The temperature and precipitation data were simulated using an autoregressive integrated moving average (ARIMA) model. With an average temperature increase of 0.20 °C every ten years, the results showed a significant warming trend. Northern, central, and southern regions saw the largest increases in minimum temperatures (from 0.80 to 2.4 °C), while southern and southeastern regions saw the largest increases in maximum temperatures (1.20 to 2.48 °C). Although pre-monsoon and post-monsoon rainfall showed declines of 0.75 mm and 0.55 mm per year, respectively, with significant variability in these seasons (44.84% and 85.25%, respectively), annual precipitation showed an upward trend (+7.13 mm per year). Projections for 2011–2020 suggest a temperature rise of 0.018 °C annually, potentially resulting in a 1.0 °C increase compared to 1971. Minimum temperatures are expected to rise more sharply (0.20 °C) than maximum temperatures (0.16 °C). Annual precipitation is predicted to decrease by 153 mm, with drying conditions anticipated in northwestern, western, and southwestern regions during pre- and post-monsoon periods.